Health benefits from devolution in England: international lessons. Issue 1087 (23rd February 2016) - Doyle, Yvonne; Johnstone, Paul
Abstract: The Chancellor of the Exchequer's recent announcements to devolve decision making power from Whitehall to 30 English regions provide a challenge to use devolution to deliver more favourable health outcomes. However evaluation of devolved health models internationally is scarce, because it is rarely considered. Evidence from countries with long-standing experience of devolution finds that the best approaches are holistic, seeking fiscal freedoms to sustain the environment, promote health, well-being and citizen engagement. Overall, international outcomes are mixed, with some evidence of greater efficiency of care delivery but little hard evidence of better clinical outcomes or health status. Handling specialised services in a devolved health system is challenging. Regulation by national authorities is important to avoid gaming of the system by providers. Information from the devolved area is important in demonstrating equitable access. We present an evaluation framework and recommend that evaluation continues through governance of these deals during implementation.